A mediation analysis to explain socio‐economic differences in bladder cancer survival. (26th August 2020) - Russell, Beth; Hemelrijck, Mieke V.; Gårdmark, Truls; Holmberg, Lars; Kumar, Pardeep; Bellavia, Andrea; Häggström, Christel
Abstract: Introduction: This study aims to disentangle heterogeneity in the survival of bladder cancer (BC) patients of different socioeconomic status (SES) by identifying potential mediators of the relationship. Methods: The Bladder Cancer Database Sweden (BladderBaSe) was used to select patients diagnosed between 1997 and 2014 with Tis/Ta‐T4 disease. The education level was used as a proxy for SES. Accelerated failure time models were used to investigate the association between SES and survival. Mediation analysis was used to investigate potential mediators of the association also accounting for interaction. Results: The study included 37 755 patients from the BladderBaSe. Patients diagnosed with both non‐muscle invasive bladder cancer (NMIBC) and muscle‐invasive bladder cancer (MIBC) who had high SES were found to have increased overall and BC‐specific survival, when compared to those with low SES. In the NMIBC patients, Charlson Comorbidity Index was found to mediate this relationship by 10% (percentage of the total effect explained by the mediator) and hospital type by 4%. The time from referral to TURBT was a considerable mediator (14%) in the MIBC patients only. Conclusions: Mediation analysis suggests that the association between SES and BC survival can be explained by several factors. The mediators identified were not, however, able to fully explain the theoretical causal pathway between SES and survival, therefore, future studies should also include the investigation of other possible mediators to help explain this relationship further. These results highlight the importance of standardization of clinical care across SES groups. Abstract : This is the first time a study has aimed to disentangle the heterogeneity in survival outcomes in bladder cancer by identifying any potential mediators of the relationship between SES and survival. These results highlight the importance of standardization of clinical care across SES groups.